The role of the basics of manufacturing systems in achieving production efficiency and effectiveness - an applied study in the Holy Karbala Cement Factory - Muhamad Trky abd Al-Abbas (Iraqi Journal for Administrative Sciences, 2024)
The Industrial sector in Iraq suffer the lack of the pillars intersection of efficiency and effectiveness in its work .This is obvious from the not ablate decision take of lower cost production ,the application of Production System has become a local demand in the light of the current variables ,since it saves the hardly ,Time , Cost , quickly .in the most transaction with the Operation production of the clear lack of Productivity sufficient knowledge of its aspects. The marginal productivity of both labour and capital appeared positive. The output responds highly to capital and weakly to labor. There are positive effects for intellectual capital and technical progress. The most important implication , it is beneficial for Iraqi private Karbala cement Factory to expand its Productivity and capacity.